(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The article addresses relevant issues related to the application of elements of the Task-Based Learning (TBL) methodology in teaching speaking skills in English language classes, both in general education schools and in higher educational institutions with non-linguistic profiles. The paper analyzes the extent to which this issue has been studied in the scientific and pedagogical community. It presents the specific characteristics of speaking as a form of verbal communication. The article outlines the nature of communication as a dynamic process of interaction. The goals, objectives, and methods of teaching speaking in foreign language lessons are discussed. The primary objective of teaching speaking is to develop speech skills that students can use both in academic settings and in everyday communication situations. Among the methods for developing high-level speaking skills (which should be demonstrated by senior school students and university students in non-linguistic fields), the article highlights speech exercises that teach oral language in its various forms.